Prototype development of normal Asian human skull - Nurhanis Sofiah, Abd Ghafar (2013)
Skull which is cover with scalp is skeletal structure of human’s head that protect and form a cavity for the brain, where the nervous system is. Nowadays, prototype of human’s skull model needed in wide use such as to educate and train physicians, inform patient, support R&D and for surgical planning The purpose of this study is to build a three dimensional of normal Asian human’s skull by using any applicable machine. The process of replicating human’s skull start with two dimensional Computed Tomography(CT) data that need to be translate into three dimensional rapid prototyping data by using MIMICS software. The three dimensional(3D) skull model need to be observed and measure as the scope of this project focused to specific normal Asian human. The observation of its morphological features of the skull and linear measurement had found that the 3D skull model belong to normal Asian human. Then, the 3D file images will be exported into related software for fabrication of prototype process. The prototype development had be done by using modeler machine that use subtractive concept The skull prototype that made up from chemical wood, or its specific name, miraboard 700 undergoes drop ball experiment for capability determination of the skull prototype. For validation, the drop ball test experiment result was compare to result of analytical method. The research comes out with almost the same value percentage different between the experimental and analytical method.